Atopic dermatitis on flat angioma of the median line. - Garofalo, L.; Arpaia, N.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2011)
A child of 4 ½ months presented from a few weeks hair loss in the nuchal region and within that area an itchy dermatitis. The dermatological examination showed an erythematous, scaling plaque with blurred borders in the nuchal region within an area with shorter hair (Fig. 1). After a biopsy a corticosteroid lotion was given. After 7 days the inflammation regressed and got evident a brownish-red area (Fig. 2) that bleached under the finger pressure, covered with thicker and longer hair. The histology (Fig. 4 and box) showed acanthosis, spongiosis and dilated vessels without inflammatory infiltrate in the superficial dermis. The final diagnosis was atopic dermatitis on flat median angioma with hypertrichosis due to vasodilation, all signs presenting inside the physiological hair loss of the newborn. 1 month later (Fig. 3) angioma and hypertrichosis persisted, albeit with less clinical evidence.